(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study, titled "Strategies on Brand Management in Mcking Sizzling Chicken in De Jesus Novaliches, Quezon City," was conducted intentionally by the researchers to gather data and information that may be used to make this study successful. Mcking’s sizzling strategies on their price, products, services, brand, and brand awareness are essential. Therefore, the researchers conducted this study to determine what needs improvement and what Mcking’s needs to do. The researchers used a tool called Google Forms to collect feedback from 30 customers of Mcking Sizzling Chicken. They asked customers to share their thoughts about the food, services, and brand of the restaurant. Brand strategies: the researchers found that Mckings had several tactics to attract customers. These included offering budget-friendly meals, giving priority to both physical stores and online customers, continuously developing new products, and creating engaging social media content. The most effective strategy, according to customers, was offering budget meals. The problems encountered by customers are lack of space in the parking lot and dine-in area, gristly meat, wrong orders being served sometimes, difficulty in using cutlery, delay of services, and difficulty finding their location. These problems have an impact on their brand. However, to continue growing and recognizing their brand and their business, those problems need to be prevented, and solutions need to be made by providing high standards and satisfying all customers to maintain their loyalty and retention. Mcking’s Sizzling Chicken is an aspiring small business that wants to grow as a successful business. Therefore, the researchers made suggestions and action plans. Conducted market research, Implemented a new pricing strategy, Redesigned store layout, and Trained staff on customer service. These action plans to help Mcking’s Sizzling Chicken improve their brand strategies and help them make more customers recognize their brand and grow as a successful business."